Čech systems and approximate inverse systems - Matijević, Vlasta; Rubin, Leonard R. (2020)
We generalize a result of the first author who proved that the Čech system of open covers of a Hausdorff arc-like space cannot induce an approximate system of the nerves of these covers under any choices of the meshes and the projections.
Bibliografske bilješke na kraju teksta.
Abstract.
Keywords: Aproksimativni inverzni sustavi -- Ćechov sistem